UJI EFEKTIFITAS EKSTRAK DAUN SIRSAK (Annona muricata L.) DENGAN MENGGUNAKAN BEBERAPA JENIS PELARUT TERHADAP KADAR KOLESTEROL TOTAL DARAH MENCIT PUTIH JANTAN - Sanubari Rela Tobat (Fakultas Farmasi Universitas 17 Agustus 1945 Jakarta, 2017)
The research about the effectiveness of leaves of the soursop leaves (Annona muricata L.) extracts using three types of solvents e.g ethanol 70%, ethyl acetate and hexane in lowering total cholesterol blood level of white male mice induced with food high cholesterol (MLT) and prophyltiouracil for 21 days. The study was carried out experimentally by 8 groups, that are negative control group (normal), the positive control group (hypercholesterolemia), and treatment groups (given the test preparation) with dose of 100 mg/kgBB and 200 mg/kgBB. The observed parameter is total cholesterol blood levels of white male mice after 7 days administration of preparation. The results of statistical analyzed by one way ANOVA showed the ethanol 70%, ethyl acetate, and hexane extract of the leaves of soursop (Annona muricata.L) have significant differences between groups (p<0,05). Based on the percentage decrease of blood cholesterol levels, the ethyl acetate extract dose of 200 mg/kgBB is an extract of the most effective in lowering total blood cholesterol levels of male white mice. Keywords : Blood Cholesterol Levels, Extract of Soursop Leaves, Propylthiouracil, MLT.